Converting sub-Arctic birch forests to spruce plantations : responses of predators and prey - Pedersen, Åshild Ønvik (Universitetet i Tromsø, 2010)
The papers of this thesis are not available in Munin: 1. Pedersen, Å.Ø., Yoccoz, N.G., Ims, R.A. and Sigurdsen, T.: 'Effects of non-native spruce plantations on small mammal communities in sub-Arctic birch forests', Forest Ecology and Management (2010) vol. 260, no. 3, pp. 331-338. Available at http://dx.doi.org/10.1016/j.foreco.2010.04.020 2. Sigurdsen, T., Pedersen, Å.Ø., Yoccoz, N.G., Haukisalmi, V. and Ims, R.A.: 'Are endoparasites of common shrew indicators of tree species conversion from sub-Arctic birch forest to spruce plantations?', manuscript, later published in European journal of forest research, Volume 131, Number 2 (2012), 389-400, available at http://dx.doi.org/10.1007/s10342-011-0511-7 3. Pedersen, Å.Ø., Ims, R.A., Yoccoz, N.G., Hausner V.H. and Juell, K.H.: 'Scale-dependent responses of predators and their prey to spruce plantations in sub-Arctic birch forests in winter', Ecoscience (2010) 17(2):123-136. Available at http://dx.doi.org/10.2980/17-2-3333 4. Pedersen, Å.Ø., Yoccoz, N.G. and Ims, R.A.: 'Spatial and temporal patterns of artificial nest predation in mountain birch forests', European Journal of Wildlife Research (2009) vol.55: 371-384. Available at http://dx.doi.org/10.1007/s10344-009-0253-8 5. Klausen, K.B., Pedersen, Å.Ø., Yoccoz, N.G. and Ims, R.A.: 'Prevalence of nest predators in a sub-Arctic ecosystem', European journal of wildlife research (2010) vol. no.56:221–232. Available at http://dx.doi.org/10.1007/s10344-009-0304-1 In northern Norway large areas of sub-Arctic coastal birch forests have gradually been replaced by non-native spruce plantations during the last century. Spruce planting changes the forest floor vegetation and soil conditions, increase the amount of artificial edges and alter the forest landscape mosaics. Such tree species conversions are likely to reduce or increase suitable wildlife habitat, alter animal space use patterns, habitat selection and population and community dynamics. In a spatially extensive study design using live-trapping, snow tracking and ...